Grateful leadership : using the power of acknowledgment to engage all your people and achieve superior results - Umlas, Judith W. (McGraw-Hill, 2013)
An essential approach for leaders who want to achieve the bottom line and foster a value driven workforce to build stronger professional relationships with customers, stakeholders, and employees. It shows how to create a more positive and meaningful connection between you and the people you lead.